K+ Transport in Perfluorosulfonic Acid Membranes and Its Influence on Membrane Resistance in CO2 Electrolysis. Issue 4 (29th December 2021) - Vetter, Kim‐Marie; Härtl, Jamie; Reinisch, David; Reichbauer, Thomas; Martić, Nemanja; Hinrichsen, Kai‐Olaf; Schmid, Günter
Abstract: In CO2 electroreduction it is common to use cation exchange membranes in combination with high‐molar electrolytes. In a model polymer electrolyte membrane (PEM) water electrolysis setup, which mimics CO2 electrolysis in a mixed (modemix ) and in a separate electrolyte mode (modesep ), this study investigates how K + ‐sulfonate interactions increase membrane resistance dependent on the electrolyte concentration. K + ‐based electrolytes (KHCO3, K2 SO4 ) are used instead of ultrapure water in the PEM‐model electrolyzer. At 1.0 M KHCO3, the membrane resistance is increased by 1.7 Ω cm 2 (cathode side only) to 4.2 Ω cm 2 (modemix ), causing a significant voltage increase that needs to be invested for K + transport over a PFSA membrane. We quantify the underlying ionic interactions to 527–545 mV and observed a further effect, namely a space‐charge limitation expressed by a strongly increased voltage, occurring in the case of K + overload when lacking hopping centers for cation transport. Beginning at ca. 300 mA/cm 2, the current density gets high enough to drive K + back to the cathode side and low enough to prevent large resistive contributions and K + overload. Along with thermodynamic considerations and pH‐induced intrinsic operational contributions, the membrane resistance was found to have a significant impact contributing to the total cell voltage Vtotal and proved that current research towards green and scalable CO2 electrolysis is on a promising way towards broad application. Abstract : Summing up the voltage : In this study, K + ‐sulfonate interactions were studied and how they increase membrane resistance dependent on the electrolyte concentration. Therefore, a model PEM water electrolysis setup mimicking CO2 electrolysis was used in a mixed and in a separate electrolyte mode.